The ORGANIZATIONAL COMMUNICATION IN RELATION TO LEADERSHIP AND ORGANIZATIONAL WORK BEHAVIOUR: Abstract - Pohan, Aqila Syafah Marwah; Hayati, Fitri (Journal of Educational Administration, 2023)
Leadership plays a vital role in the success of an organization. Communication is one of the important aspects concerning leadership in influencing organizational work behavior. That's why this writing study aims to find out how communication is in organizations, besides that this article also aims to identify how leadership is in organizations, at the same time the studies in writing this article also aim to analyze how to work behavior is in organizations. Meanwhile, the goal that is no less important in writing this article is to analyze how organizational communication is in relation to leadership and organizational work behavior. The findings in this study indicate that communication should come from various directions, originating from top-down, bottom-up, and horizontally within and across organizations, both formal and informal, to function informatively, regulative, persuasively, and integrative. This writing aims to determine the behavior of the leadership in the organization. The writing method uses the library research method. From the discussion, it can be concluded that leadership is a person's ability to influence and motivate others to do something in accordance with a common goal. Leadership includes the process of influencing in determining organizational goals, motivating the behavior of followers to achieve goals, influencing to improve the group and its culture.